Harmonizing Newborn Screening Laboratory Proficiency Test Results Using the CDC NSQAP Reference Materials - Charles Austin Pickens; Maya Sternberg; Mary Seeterlin; Víctor R. De Jesús; Mark Morrissey; Adrienne Manning; Sonal Bhakta; Patrice K. Held; Joanne Mei; Carla Cuthbert; Konstantinos Petritis (MDPI AG, 2020)
Newborn screening (NBS) laboratories cannot accurately compare mass spectrometry-derived results and cutoff values due to differences in testing methodologies. The objective of this study was to assess harmonization of laboratory proficiency test (PT) results using quality control (QC) data. Newborn Screening Quality Assurance Program (NSQAP) QC and PT data reported from 302 laboratories in 2019 were used to compare results among laboratories. QC materials were provided as dried blood spot cards which included a base pool and the base pool enriched with specific concentrations of metabolites in a linear range. QC data reported by laboratories were regressed on QC data reported by the Centers for Disease Control and Prevention (CDC), and laboratory's regression parameters were used to harmonize their PT result. In general, harmonization tended to reduce overall variation in PT data across laboratories. The metabolites glutarylcarnitine (C5DC), tyrosine, and phenylalanine were displayed to highlight inter- and intra-method variability in NBS results. Several limitations were identified using retrospective data for harmonization, and future studies will address these limitations to further assess feasibility of using NSQAP QC data to harmonize PT data. Harmonizing NBS data using common QC materials appears promising to aid result comparison between laboratories.